2014
DOI: 10.1016/j.semcdb.2014.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional regulation of graded Hedgehog signaling

Abstract: The Hedgehog (Hh) pathway plays conserved roles in regulating a diverse spectrum of developmental processes. In some developmental contexts, a gradient of Hh protein specifies multiple cell types in a dose-dependent fashion, thereby acting as a morphogen. Hh signaling ultimately acts on the transcriptional level through GLI proteins. In the presence of Hh signaling full length GLI proteins act as transcriptional activators of target genes. Conversely, in the absence of Hh, GLI proteins act as transcriptional r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
52
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 103 publications
1
52
0
1
Order By: Relevance
“…1B= and C=), as expected (7). This differential expression pattern of Gli1 and Gli3 in the EGL is consistent with their roles as a transcriptional activator and a repressor, respectively (27). However, we were surprised to find a very high level of Sufu in P7 EGL (Fig.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…1B= and C=), as expected (7). This differential expression pattern of Gli1 and Gli3 in the EGL is consistent with their roles as a transcriptional activator and a repressor, respectively (27). However, we were surprised to find a very high level of Sufu in P7 EGL (Fig.…”
Section: Resultssupporting
confidence: 81%
“…Downstream from the Ptch1-Smo receptor system, the signaling responses are orchestrated by three Krüppel family transcription factors, Gli1, Gli2, and Gli3, each of which uses a highly conserved zinc finger DNA-binding domain to bind a common cis-acting DNA element in target gene promoters (24)(25)(26)(27). Early data from Drosophila showed that the fly Gli-homologous protein encoded by cubitus interruptus (Ci) undergoes a partial proteolysis that converts the full-length 150-kDa protein into a carboxylterminally truncated 75-kDa transcriptional repressor, Ci 75D , in unstimulated cells (28).…”
mentioning
confidence: 99%
“…The increased GLIFL to GLIR ratio posed two possible molecular mechanisms for producing HH-dependent midfacial widening: (1) a loss of GLIR activity (de-repression) [44], or (2) a gain of GLIA activity. Using genetic and biochemical approaches, we attempted to determine which mechanism was responsible for midfacial widening in ciliopathic mutants.…”
Section: Resultsmentioning
confidence: 99%
“…How various combinations of Gli activators and repressors control Hh target gene expression and confer graded Hh responses in the nucleus is a major unresolved issue in Hh signaling (Hui and Angers 2011;Rabinowitz and Vokes 2012;Falkenstein and Vokes 2014). This task is particularly challenging because different tissues use a unique combination of Gli activator/repressor to produce specific Hh outputs (i.e., a specific set of Hh targets) necessary for patterning.…”
mentioning
confidence: 99%